Spontaneous Sphenoid Wing Meningoencephaloceles with Lateral Sphenoid Sinus Extension: The Endoscopic Transpterygoid Approach - Ajlan, Abdulrazag; Achrol, Achal; Soudry, Ethan; Hwang, Peter H.; Harsh, Griffith (Journal of Neurological Surgery Part B: Skull Base, 2014)
Spontaneous meningoencephalocele (SME) of the sphenoid wing is a rare cause of cerebrospinal fluid (CSF) leakage. Surgical closure of the fistula is usually required. The approach taken depends on the location of the defect and the extension of the meningoencephalocele. The endoscopic transpterygoid approach may be useful. We prospectively analyzed the three cases of SME of the sphenoid wing with lateral sphenoid sinus extension treated endoscopically at Stanford over the last 3 years with regard to imaging findings, operative technique, and operative morbidity. In our three cases, the extent of pterygopalatine fossa (PPF) exposure undertaken, complete in one and partial in two, depended on the defect site. Follow-up ranged from 17 to 25 months. The fistula was completely closed in all three cases. Extant literature reports a 97% rate of successful closure (N = 65 of 67, with a mean follow-up of 25 months) and no major complications. Endoscopic transpterygoid repair is a useful, safe alternative to traditional approaches for repair of SME of the sphenoid wing. Its feasibility depends on the site of the defect, which can be identified by preoperative imaging. Larger PPF exposure and postoperative lumbar drainage of CSF can be useful and have a low risk of morbidity.
Keywords: endoscopic; transpterygoid; meningoencephalocele; sphenoid wing